Uniform ; The Power of Masculine Identity - Hendhy Nansha; Setiawan Sabana (JURNAL RUPA, 2019)
Identity is a very important aspect of human life. The definition of the self is a characteristic which distinguishes each person. In a certain situation, an identity could mean anxiety, fear, or ego. This happens when someone is in a rather defensive position. Jean Baudrillard, one of post-modernist has denounced the existence of a definite identity that latched into a subject since he believes that everything has deconstructed. Physiologically, identity can not be separated from the body. Representation is crucial for people to interpret the body as a battlefield, discourses of what emerged there, and various things that affect in creative practice. Uniform is also closely linked to identity and the body. Uniform can be central for the construction of identity. We can identify whether the person is a member of the police, armed forces, and so on by simply take a look at the uniform that he uses. In a masculinity viewpoint, sometimes a person who wears uniform feel himself the most powerful (arrogant) and become cruel for people around him. This paper aims to expose my anxiety toward patriarchal culture that is built up from a uniform which I transformed as a basis for my artwork creation.